Attitudes of young Poles and Norwegians towards audiovisual translation in cinema and broadcast media - Awedyk, Witosław (Folia Scandinavica Posnaniensia, 2016)
This paper is a contribution to the discussion on audiovisual translation (AVT) in cinema and broadcast media on the example of Poland and Norway seen from the perspective of viewers. It aims at establishing possible differences and similarities in the way dominant AVT modes are viewed by younger people in these two countries. In AVT studies Norway has always been classified as a subtitling country while Poland has traditionally been associated with cinema subtitling and television voice-over, of which the latter often baffles AVT scholars. Consequently, one may presume that the audiences in these two countries are likely to have fairly disparate expectations towards AVT modes used in their cinemas and broadcast media. For the purpose of this article a questionnaire has been prepared and the findings arising from the analysis of the submitted replies will be presented here.